Influence of Meteorological Parameters on Air Pollution Propagation in an Active Dumpsite In Abeokuta, Nigeria - A.T, Mustapha; A, Sobowale; O.J, Adeosun; A.A, Badejo (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Air pollution from dumpsites is a growing concern due to its detrimental effects on both human health and the environment. This study examines the influence of meteorological parameters on the propagation of air pollution from a dumpsite, focusing on the Saje dumpsite in Abeokuta, Nigeria. The concentration of the air pollutants; particulate matters (PM2.5, PM10), formaldehyde (HCHO), total volatile organic compound (TVOC), carbon monoxide (CO), oxygen (O2) and selected meteorological factors (wind speed, wind direction, temperature and humidity) were measured using portable handheld gas detectors. Multiple linear regression (MLR) and multiple nonlinear regression (MNLR) models were employed to predict the relationship between the meteorological parameters and the air pollutants using XLSTAT® 2018 modelling software. Regression analysis showed that, the coefficient of determination (R2) ranged from 0.114 – 0.157 (dry season sampling) and 0.006 – 0.319 (wet season sampling) for MLR and 0.466 – 0.673 (dry season sampling) and 0.390 – 0.671 (wet season sampling) for MNLR models. The MNLR model is best used in predicting the air pollutants concentration propagation using meteorological parameters as predictors. This finding emphasizes the significant role of meteorological parameters in influencing air pollution dynamics. As such, the study recommends the adoption of MNLR models for more accurate predictors and effective management of air pollution from dumpsites.